Local Identity in Southeastern Lithuania at the Beginning of the 21st Century - Tuomienė, Nijolė (Taikomoji kalbotyra, 2025)
The study, based on empirical data collected at the beginning of the 21st century from 17 Lithuanian Language Atlas (LLA) points in the Šalčininkai district, aims to answer several questions: Under what circumstances did the local identity of multilingual people form and why did a significant group of people in the region choose to call themselves as locals (Lith. tuteišiai, Bel. тутэйшыя, мясцовыя, Pol. tutejszy, miejscowy)? The study aims to reveal the current consequences of this previously accepted choice of the population. After analysing sociolinguistic surveys of residents, recorded group discussions, and in-depth interviews with respondents, it can be stated that most respondents who call themselves locals, identify themselves as Poles. Most of the older villagers interviewed speak the Belarusian dialect po prostu (Eng. simple speech) in everyday life, the middle generation communicates mainly in Russian and Polish, and the younger generation communicates mainly in Polish, Russian, and Lithuanian.Qualitative data analysis showed that the concept of identity of different generations of residents of Southeastern Lithuania is constantly changing, albeit slowly and insignificantly. The boundaries of ethnic identities in the region remain unclear. The processes of identity change in the Šalčininkai district have not yet been completed. Poles in the district often describe their regional identity with other categories, which determine identification with local areas. The study allows us to predict that regional local identity is gradually decreasing, and other forms of identification are strengthening, primarily ethnic (more characteristic of the middle generation of residents) and civic (more characteristic of the younger generation of residents) identities.